Urban planning and climate change in Ghana - Patrick Brandful Cobbinah; Michael Osei Asibey; Marcia Opoku-Gyamfi; Charles Peprah (Journal of Urban Management, 2019)
Urban planning is commonly blamed for its failure to exert a positive influence on managing climate change impacts in urban Africa; yet little is known about planning agencies' perspectives on climate change-urban planning conundrum, and corresponding policy responses. It is in response to this gap, this paper explores agency perspectives and policy responses on the possibility and procedure for harnessing urban planning as a tool for managing climate change impacts in a Ghanaian city of Kumasi. Using a review of three relevant urban planning and climate change policies of Ghana, and interviews with six urban planning and climate-related agencies in Kumasi, findings indicate a demonstration of an unclear nature of policies, and a lack of focus on climate change issues in urban planning. Evidence of weak agency framework and coordination challenges (e.g., logistics, enforcement of laws) were reported, a situation that has contributed to the city's inability to manage "normal" climate change impacts (e.g., flash floods). The paper concludes with proposals for incorporating climate change concerns into urban planning in Ghana.
Keywords: 710; Climate change; Kumasi; Planning policy; Urban planning; Urbanisation